"Driver-passenger" bacteria and their metabolites in the pathogenesis of colorectal cancer. (1st January 2021) - Avril, Marion; DePaolo, R. William
ABSTRACT: Colorectal cancer (CRC) is a significant public health problem accounting for about 10% of all new cancer cases globally. Though genetic and epigenetic factors influence CRC, the gut microbiota acts as a significant component of the disease's etiology. Further research is still needed to clarify the specific roles and identify more bacteria related to CRC development. This review aims to provide an overview of the "driver-passenger" model of CRC. The colonization and active invasion of the "driver(s)" bacteria cause damages allowing other commensals, known as "passengers, " or their by-products, i.e., metabolites, to pass through the epithelium . This review will not only focus on the species of bacteria implicated in this model but also on their biological functions implicated in the occurrence of CRC, such as forming biofilms, mucus, penetration and production of enterotoxins and genotoxins.